2012
DOI: 10.1055/s-0032-1312588
|View full text |Cite
|
Sign up to set email alerts
|

Does Listening to Music With an Audio Ski Helmet Impair Reaction Time to Peripheral Stimuli?

Abstract: With the recent worldwide increase in ski helmet use, new market trends are developing, including audio helmets for listening to music while skiing or snowboarding. The aim of this study was to evaluate whether listening to music with an audio ski helmet impairs reaction time to peripheral stimuli. A within-subjects design study using the Compensatory-Tracking-Test was performed on 65 subjects (36 males and 29 females) who had a mean age of 23.3 ± 3.9 years. Using repeated measures analysis of variance, we fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 13 publications
0
4
1
Order By: Relevance
“…Verbal warnings alerting one to danger, though typically loud, may be affected by helmet use 34. However, a recent study failed to find an association between listening to music through a helmet and response time to peripheral stimuli 15. Banning personal music players while snowboarding in a TP would be logistically difficult and require considerable and expensive enforcement efforts and our findings do not suggest that it would reduce injuries.…”
Section: Discussioncontrasting
confidence: 53%
See 1 more Smart Citation
“…Verbal warnings alerting one to danger, though typically loud, may be affected by helmet use 34. However, a recent study failed to find an association between listening to music through a helmet and response time to peripheral stimuli 15. Banning personal music players while snowboarding in a TP would be logistically difficult and require considerable and expensive enforcement efforts and our findings do not suggest that it would reduce injuries.…”
Section: Discussioncontrasting
confidence: 53%
“…In a laboratory setting, Ruedl et al 15 found that listening to music through an audio ski/snowboard helmet shortened reaction time to peripheral stimuli compared with those not listening to music 15. The authors explained this by the motivational properties of music, which have been linked to increased motor coordination and peak power output16 17; however, the relationship between listening to music while snowboarding and injury is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Injured slope tourers reported that they were listening to music during downhill skiing more often compared to non-injured slope tourers [13]. However, listening to music did not result in an increased reaction time to peripheral signals [14]. It might be possible that balance is affected by listening to music (instead of reaction time).…”
Section: Introductionmentioning
confidence: 99%
“…The unadjusted result indicated that listening to music reduced the odds of injury. In a laboratory setting, sport students listening to music while wearing a helmet with built-in speakers had similar mean reaction time to peripheral stimulus as those who were wearing a helmet but not listening to music 38. Similar to non-TP research, snowboarding in suboptimal environmental (bad weather/visibility) conditions affected the odds of injury 9.…”
Section: Discussionmentioning
confidence: 67%